Utilization of Tiktok as a Social Media Platform for Tourism Promotion in Kepyar Village, Purwantoro District, Wonogiri Regency - Ramelan, Agus; Adriyanto, Feri; Warindi, Warindi; Saputro, Joko Slamet; Sulistyo, Meiyanto Eko; Faishol, Fahmi; Novitasari, Purwati Eka; Cahyaningrum, Sakira Elen (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Kepyar Village, located in Purwantoro District, Wonogiri Regency, possesses significant potential for the development of natural tourism due to its lush and pristine environment. However, despite its scenic beauty, the village remains relatively underpromoted, resulting in limited tourist visits, predominantly from nearby areas. This study explores the use of TikTok as a promotional tool to enhance the visibility of Kepyar Village as a tourist destination. By utilizing TikTok for destination branding, the village aims to attract a wider audience, thereby benefiting the local economy and community. The initiative is expected to raise broader public awareness about Kepyar Village’s tourism potential, contributing not only to its reputation as a tourist village but also providing an economic avenue for residents to improve their livelihoods.